2016
DOI: 10.3233/wor-162297
|View full text |Cite
|
Sign up to set email alerts
|

Developing a workplace resilience instrument

Abstract: An instrument to measure individual resilience in the workplace (WRI) was developed. The WRI's four factors identify dimensions of workplace resilience for use in subsequent investigations: Active Problem-Solving, Team Efficacy, Confident Sense-Making, and Bricolage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 31 publications
2
62
0
Order By: Relevance
“…The authors also proposed that RAW scale is a more realistic and practical measure affecting workplace resilience and suggested that the scale dimensions could be useful indicators to build a resilience balance scorecard. Mallak and Yildiz (2016) also argued that there is a dire need for developing a standardized instrument in workplace setting to measure resilience of employees.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also proposed that RAW scale is a more realistic and practical measure affecting workplace resilience and suggested that the scale dimensions could be useful indicators to build a resilience balance scorecard. Mallak and Yildiz (2016) also argued that there is a dire need for developing a standardized instrument in workplace setting to measure resilience of employees.…”
Section: Discussionmentioning
confidence: 99%
“…Connor and Davidson () viewed resilience as having the ability to successfully cope with adversity. For example, individuals who have witnessed or endured hardship, such as war (Ferguson, Sperber Richie, & Gomez, ), in an organization (Kornhaber & Wilson, ), or in a home environment (Anderson, Renner, & Danis, ) or the workplace (Mallak & Yildiz, ), have the potential to build resilience when social support and psychological stamina are harnessed. Resilience may be a key characteristic influencing the attitudes and responses of SCI survivors to their injury and rehabilitation although there is limited research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…In order to extract a deeper understanding of the real or apparent nature of posited gender influences, it is suggested, from the influence of resilience and risk-taking which were predictive for women's motivation, that coming investigations ought to be devoted to the recruitment utility propensity of the JMT instrument through coadministration with the Workplace Resilience Instrument which optimizes factors involving "active problem-solving", "team efficacy", confident "sense-making" and "bricolage" [23].…”
Section: Limitationsmentioning
confidence: 99%
“…Thus, in an industrial setting, female-dominated industries exhibited greater interpersonal-orientation than the male-dominated industries, with the former reporting more pressure from their positions [22]. The influence of gender upon leadership styles, as well as stress and mental health, seems essential to understanding leadership efficacy not least with regard to workplace resilience [23]. In this regard, the question arises as to whether or not leadership development initiatives promote leadership strengths for both genders or whether leadership strengths vary with position/culture in the context of: (i) equal access to resources and opportunities, (ii) minimizing unconscious gender bias, (iii) enhancing work-life balance, and (iv) promoting leadership engagement [24].…”
Section: Introductionmentioning
confidence: 99%